PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN DALAM PENERAPAN METODE FONIK PADA KELAS I SDN 20 PIAI KOTA PADANG - Yones Atrasia; Adrias; M. Habibi; Fikhen Tri Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of beginning reading skills among first-grade students at SDN 20 Piai, Padang City. The preliminary observation revealed that only 10 out of 28 students (35.71%) achieved the minimum mastery criterion, with a class average score of 70.00. This study aimed to describe: (1) the lesson planning, (2) the implementation of learning activities, and (3) the improvement of students' beginning reading skills through the application of the Phonics method. This study employed Classroom Action Research (CAR) using qualitative and quantitative approaches based on the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection. The research was conducted in two cycles, with two meetings in Cycle I and one meeting in Cycle II. Subjects were 28 first-grade students of SDN 20 Piai, Padang City. Data were collected through observation, tests, and documentation, and analyzed using qualitative and quantitative techniques. The findings showed that the implementation of the Phonics method improved the quality of lesson planning, classroom implementation, and students' beginning reading skills. The lesson plan assessment increased from an average of 85.40% in Cycle I to 95.80% in Cycle II. Teacher activity improved from 85.90% to 96.80%, while student activity increased from 84.30% to 97.50%. Students' beginning reading scores improved from a class average of 70.00 in the preliminary condition to 77.50 in Cycle I and 86.07 in Cycle II. Classical learning mastery increased from 35.71% to 85.71% in Cycle II. Therefore, the Phonics method effectively improved the beginning reading skills of first-grade students at SDN 20 Piai, Padang City.